Developing Communication Technologies and Transaction Costs: A Note - Tamara Todorova (Proceedings of the Contemporary Economic and Financial Problems in the Economy Conference of Young Scholars, June 5, 1998, 1999)
The paper discusses the role of communication technologies in reducing the costs of using market exchange. It analyzes the comparative effect of new technologies on transactions which take place within and outside the firm using Coase's postulate of the size of the firm. Technologically innovative firms in which technologies have the effect of essentially reducing the costs of internal organization would expand the size of firms. These are usually communication technologies having the effect of reducing the spatial distribution among factors of production. Communication and other technologies would have the effect of reducing the size of firms when they facilitate market transactions and reduce the costs of carrying out market exchange more than they affect transactions within the firm.
Keywords: D21; D23; O31; 330; transaction costs; communication technologies; vertical integration